Demographic and clinical features associated with dengue fever during an outbreak in North India - Nazir, Sadat; Salgotra, Sahil; Chowdri, Iqra Nisar (International Journal Of Community Medicine And Public Health, 2023)
Background: Dengue is a viral mosquito borne disease that poses high medical burden in many regions of the world. Early diagnosis and prompt treatment are critical in reducing the overall morbidity and mortality associated with dengue fever. So, this study was conducted to study the overview of dengue fever and its clinical manifestations during an outbreak in patients in a tertiary care hospital. Methods: It was a cross sectional study which was conducted at a tertiary care hospital GMC Jammu. Nonprobability convenience sampling technique was used to enroll the study participants. Results: The 222 dengue patients were included in this study with mean age of the patients 33.2±11.32 SD years. Among the dengue patients, 74 (33.3%) tested positive for antigen Ns1Ag. IgM antibodies was positive in 20 (9.0%), IgG antibodies was positive in 10 (4.5%) and 18 (8.1%) of the patients tested positive for both IgG and IgM antibodies. Overall prevalence of antibodies that are specific to dengue was 22%. Conclusions: Dengue specific antigen was present in most of the patients. The major clinical and laboratory outcomes were fever, myalgia, headache/joint pain/body aches, diarrhea and vomiting. An overall prevalence of 22% of dengue specific antibodies was found in the patients.